Health Impacts of Exposure to Heavy Metals in Some Selected Lipstick Products Available in Mashhad, Iran - Hossein Alidadi; Sima Zamand; Aliasghar Najafpoor; Hamid Heidarian; Aliakbar Dehghan; Maryam Sarkhosh; Vahid Taghavimanesh (Hamadan University of Medical Sciences, 2019)
This study aimed to investigate the levels of heavy metals in the lipstick products. In general, 30 samples were randomly selected from Mashhad markets. Analysis of variance (ANOVA) and t test were used to compare color and price variables. Based on the results, the mean concentrations of studied elements were as follows: Cd (ND-0.52 µg/g), Cr (0.25-76.35 µg/g), Ni (ND-20.12 µg/g), Zn (ND-224.22 µg/g), Pb (ND-44.77 µg/g), and Hg (ND-0.32 µg/g). The presence of toxic metals in the samples, and on the other hand, continuous use and unintended ingestion of these metals can lead to their biological accumulation in the human body, thereby causing the development of different diseases. Hence, it deems necessary to apply suitable actions for the improvement of quality control over these products.